How a structured selection process increases the probability of hiring the best candidate and as a result, increases a company’s performance. - CHAMBERS, WILLIAM (2016)
When managers recruit for a role, they often conduct the interview in an unstructured way and hire whom they believe is the right fit for the role. Even though they may be aware of the need to select for talent, managers are often under time pressure to fill the vacant position or lose the open headcount, so they simply hire to fill the vacancy.